2019
DOI: 10.1080/02670836.2019.1661648
|View full text |Cite
|
Sign up to set email alerts
|

The titanium structure after a thermoplastic compression at elevated temperatures

Abstract: In the biomedicine, titanium with the refined grain is of great demand. The microstructure of the Grade 2 titanium samples was produced by the plastic forming at elevated temperatures and with different strain rates. Sellers–Tegartt equation was applied to verify that plastic forming stresses required to achieve the desired structure. Microstructure was observed with scanning electron and transmission electron microscopes. To characterise the elements of the structure, the electron backscatter diffraction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The most desirable changes were noted for the deformation performed at 400 °C, with strain rates 0.1/s and 1/s. As indicated in previous report [5], very desirable grain reduction was also achieved at 600 °C, so we can safely assume that temperature 500 °C is also viable for this process. The DRX was noted for the deformation at 400 °C and 10/s strain rate, causing grain growth.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The most desirable changes were noted for the deformation performed at 400 °C, with strain rates 0.1/s and 1/s. As indicated in previous report [5], very desirable grain reduction was also achieved at 600 °C, so we can safely assume that temperature 500 °C is also viable for this process. The DRX was noted for the deformation at 400 °C and 10/s strain rate, causing grain growth.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, the material strengthening is paramount. Previous research [5] indicates that one of the best ways to strengthen the material is by its grain size reduction (according to Hall-Petch theorem) [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, Arrhenius equation was chosen as the potentially most promising. However, our experimental and analytical studies showed that this equation was accurate in the case of the pure titanium only in certain circumstances [20,21]. Therefore, other models were taken into consideration.…”
Section: Introductionmentioning
confidence: 94%